Egyptian Memorials in Modern Rome: The Dogali Obelisk and the Altar of the Fallen Fascists - Weststeijn, A.V. (Edizioni Quasar, Rome, 2018)
This chapter explores the manifold meanings performed by ‘Egyptian’ monuments in modern Rome through a discussion of one of the most striking remnants of the Iseum Campense: the obelisk excavated by Rodolfo Lanciani in 1883, also known as the Dogali obelisk. It traces the convoluted public history of the obelisk since its excavation until today and explores the connection with another ‘Egyptian’ object: the pedestal of the Sallustian obelisk, which was turned into the altar of the fallen fascists on the Capitol in 1926. Describing the different phases in the modern biographies of the two memorials, the chapter shows the variety of symbolism attached to them as signifiers of regal dynasty, nationalist imperialism, fascist martyrdom and vindication, subaltern resistance and, ultimately, postcolonial oblivion. The resulting story reveals the continuous tension in the uses and meanings of the two monuments as both Roman and non-Roman objects, a tension that arguably defines aegyptiaca Romana throughout history.